Case Report: Re-irradiation of out-of-field recurrence of malignant phyllodes tumors of the breast after adjuvant radiotherapy - Li, Ziwei; Zhong, Juan; Shi, Yingying; Lu, Wenliang; Lu, Yanjv; Ge, Ning (Frontiers in Oncology, 2026)
IntroductionPhyllodes tumor of the breast (PTB) is a rare fibroepithelial neoplasm, classified as benign, borderline, and malignant. They typically present as solitary, painless, firm masses with potential rapid enlargement, and 20% exceed 10 cm, often indicating malignancy. Local recurrence frequently occurs within two years postoperatively. While the survival benefit of adjuvant radiotherapy remains controversial, it significantly reduces recurrence rates. We report a 27×14 cm malignant PTB and evaluate optimal radiotherapy strategies and re-irradiation safety in recurrent cases.Case reportA 55-year-old female presented with a rapidly enlarging left breast mass, initially detected seven years prior, measuring 50×40 cm on physical examination. The patient underwent complete surgical excision, with a postoperative pathological mass measuring 27×14 cm, followed by adjuvant radiotherapy (50 Gy/25 fractions). One month after radiation, a 15×15 cm axillary recurrence was resected (10×8 cm specimen). Two months later, a 10×8 cm infraclavicular recurrence was excised (6×5 cm specimen). Subsequently, six cycles of epirubicin–cyclophosphamide chemotherapy and re-irradiation (45–60 Gy/25 fractions) were administered. At present, there is no evidence of local recurrence.ConclusionsThis case highlights the potential role of adjuvant RT in reducing recurrence and the feasibility of carefully selected re-irradiation for recurrent MPTs. Prospective studies are needed to define optimal target volume of radiotherapy, dose fractionation, and the safety of re-irradiation.